If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(2f + 8) = 24 Reorder the terms: 6(8 + 2f) = 24 (8 * 6 + 2f * 6) = 24 (48 + 12f) = 24 Solving 48 + 12f = 24 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-48' to each side of the equation. 48 + -48 + 12f = 24 + -48 Combine like terms: 48 + -48 = 0 0 + 12f = 24 + -48 12f = 24 + -48 Combine like terms: 24 + -48 = -24 12f = -24 Divide each side by '12'. f = -2 Simplifying f = -2
| 3x-3=6x-2 | | 4/5(x-10)=4(8-x) | | ln(4x+11)=2 | | (-3m)-5=2m-15 | | -5a^2-10a+40=0 | | 14x-5x=12 | | 6x-11=-73-6x | | 3x+2y=2.50 | | 4(2d-5)=12 | | 2n+7n-10=2n-3n+10 | | -2q=88-5q | | x/180=70 | | 12+2n= | | -2k^2-7k+19=0 | | y=9+9 | | y=1+9 | | 2.5*3.5*h=35 | | 12y^3+13y^2+3y=0 | | (3m-3)/6=12 | | 7x^2y^2-3xy+4x^2y^2-8xy= | | -6(-12x-10)= | | 48=x^2-4 | | 2.3+6.9= | | 6(-12x+10)= | | -3n^2-5n+8=0 | | -12(-6x+5)= | | 2x+5y=2.95 | | x-15=2x-3 | | 5(x+2)-3=3x+15 | | -26+3=-39+14x | | -12(6x-5)= | | 5v^2+11v-42=0 |